2018
DOI: 10.1016/j.celrep.2018.01.001
|View full text |Cite
|
Sign up to set email alerts
|

CD209a Synergizes with Dectin-2 and Mincle to Drive Severe Th17 Cell-Mediated Schistosome Egg-Induced Immunopathology

Abstract: SUMMARY The immunopathology caused by schistosome helminths varies greatly in humans and among mouse strains. A severe form of parasite egg-induced hepatic granulomatous inflammation, seen in CBA mice, is driven by Th17 cells stimulated by IL-1β and IL-23 produced by dendritic cells that express CD209a (SIGNR5), a C-type lectin receptor (CLR) related to human DC-SIGN. Here, we show that CD209a-deficient CBA mice display decreased Th17 responses and are protected from severe immunopathology. In vitro, CD209a au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(53 citation statements)
references
References 44 publications
3
50
0
Order By: Relevance
“…Still, fucosylated Lewis x antigen, a known hDC-SIGN ligand, mediated suppression and tolerance to transplantation through mDC-SIGN + monocyte-derived macrophages ( 35 ). In addition, a recent study on mDC-SIGN functioning during schistosome egg infection revealed the capacity of mDC-SIGN to signal via Raf-1 depending on its carbohydrate recognition domain and affect DC functioning ( 36 ). Therefore, studies aimed at investigating DC-SIGN functioning in vivo that rely on recognition of specific glycan structures should take the ligand-binding specificity into consideration, as well as the capacity of mDC-SIGN to affect intracellular signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Still, fucosylated Lewis x antigen, a known hDC-SIGN ligand, mediated suppression and tolerance to transplantation through mDC-SIGN + monocyte-derived macrophages ( 35 ). In addition, a recent study on mDC-SIGN functioning during schistosome egg infection revealed the capacity of mDC-SIGN to signal via Raf-1 depending on its carbohydrate recognition domain and affect DC functioning ( 36 ). Therefore, studies aimed at investigating DC-SIGN functioning in vivo that rely on recognition of specific glycan structures should take the ligand-binding specificity into consideration, as well as the capacity of mDC-SIGN to affect intracellular signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it is dependent on ω1 RNase activity in addition to its native glycosylation, enabling the molecule to bind to the mannose receptor on dendritic cells and be internalized ( 49 , 50 ). It is noteworthy that both α1 and ω1 within SEA are glycoproteins, with many functional activities of such egg molecules being glycan dependent, requiring interactions with selected C-type lectin receptors on immune cells ( 51 54 ).…”
Section: Differences In Granulomatous Inflammation Of Liver and Intesmentioning
confidence: 99%
“…In addition, CD209a (C-type lectin receptor), expressed on DCs, also proved to be essential for the development of Th17 cell responses in murine schistosomiasis (61, 69). CD209a-deficient CBA mice had decreased Th17 responses and developed reduced egg-induced liver immunopathology (69,70). Clinical studies also demonstrated the positive correlation between the percentage of Th17 cells and bladder pathology in S. haematobium-infected children (62).…”
Section: Th17/il-17 Exacerbate the Egg-induced Liver Immunopathologymentioning
confidence: 99%